A highly efficient solution and solid state ESIPT fluorophore and its OLED application. (28th January 2021) - Trannoy, Virgile; Léaustic, Anne; Gadan, Sophie; Guillot, Régis; Allain, Clémence; Clavier, Gilles; Mazerat, Sandra; Geffroy, Bernard; Yu, Pei
Abstract : Readily accessible and functionalized ESIPT dyes with high fluorescence quantum yield in solution, including water, and in crystalline state are presented. Abstract : We present herein the synthesis and photophysics of 2, 2′-bipyridine-3, 3′-diol-5, 5′-dicarboxylic acid ethyl ester (BP(OH)2 DCEt2 ), an excited state intramolecular proton transfer (ESIPT)-based fluorophore featuring two identical intramolecular hydrogen bonds. BP(OH)2 DCEt2 emits efficiently not only in solution, including protic solvents ( λ em = 521 nm, Φ f = 40 to 75%), but also in crystalline state ( λ em = 530 nm, Φ f = 51%). In addition, its saponified form (Na2 BP(OH)2 DC) is highly fluorescent in water ( λ em = 490 nm, Φ f = 51%). Finally, the good electroluminescence performance of BP(OH)2 DCEt2 is also demonstrated in an OLED device.